1990
DOI: 10.1295/polymj.22.1015
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Polyamide by Interfacial Polycondensation of Dichloroformyl-Containing γ-Lactone with Hexamethylenediamine

Abstract: ABSTRACT:(2R*,4S*)-4-chloroformyl-2-chloroformylmethyl-2,4-dimethyl-4-butanolide was prepared by the chemical transformation of I-butyl methacrylate dimer telomerized using bromotrichloromethane. The interfacial polycondensation of this acid dichloride with hexamethylenediamine was accompanined by a partial hydrolytic cleavage of the lactone ring and gave an unique 6,6-type polyamide containing both lactone rings and hydrophilic groups such as carboxyl-and hydroxyl-groups. To determine the optimal conditions f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

1992
1992
2005
2005

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 9 publications
1
0
0
Order By: Relevance
“…This is in good agreement with the previous research on nylons containing the odd number CH 2 units 9–17. In the previous researches, it was found that some nylons exhibit the orthorhombic crystal systems 36–39. However, the ED and WAXD results do not match well with this orthorhombic crystal structure.…”
Section: Resultssupporting
confidence: 91%
“…This is in good agreement with the previous research on nylons containing the odd number CH 2 units 9–17. In the previous researches, it was found that some nylons exhibit the orthorhombic crystal systems 36–39. However, the ED and WAXD results do not match well with this orthorhombic crystal structure.…”
Section: Resultssupporting
confidence: 91%